Evaluation of novel slim biopsy forceps for diagnosis of biliary strictures: Single-institutional study of consecutive 360 cases (with video) - Yamamoto, Kenjiro (World J Gastroenterol, 2017)
AIM: To evaluate the feasibility and reliability of endoscopic transpapillary bile duct biopsy for the diagnosis of biliary strictures. METHODS: A total of 360 patients (241 men) who underwent endoscopic retrograde cholangiopancreatography for biliary strictures with biopsy from April 2012 to March 2016 at Tokyo Medical University Hospital were retrospectively reviewed. This study was approved by our Institutional Review Board (No. 3516). Informed consent was obtained from all individual participants included in this study. The biopsy specimens were obtained using a novel slim biopsy forceps (Radial Jaw 4P, Boston Scientific, Boston, MA, United States). RESULTS: The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were 69.6%, 100%, 100%, 59.1%, and 78.8%, respectively. The sensitivity was 75.6% in bile duct cancer, 64% in pancreatic cancer, 61.1% in gallbladder cancer, and 57.1% in metastasis. In bile duct cancer, a lower sensitivity was observed for perihilar bile duct stricture (68.7%) than for distal bile duct stricture (83.1%). In terms of the stricture lengths of pancreatic cancer, gallbladder cancer, and metastasis, a longer stenosis resulted in a better sensitivity. In particular, there was a significant difference between pancreatic cancer and gallbladder cancer (P < 0.05). One major complication was perforation of the extrahepatic bile duct with bile leakage. CONCLUSION: Endoscopic transpapillary biopsy alone using novel slim biopsy forceps is feasible and reliable, but restrictive. Biopsy should be performed in consideration of the stricture level, stricture length, and cancer type.